Peran Pondok Pesantren Sebagai Lembaga Pendidikan Islam di Indonesia - Tatang Hidayat; Ahmad Syamsu Rizal; Fahrudin Fahrudin (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2018)
This present study aims at identifying the role of Islamic boarding schools as Islamic educational institutions in Indonesia. This study employed a qualitative approach and literature study method. Based on the results of the study, Islamic boarding schools in fact provided the process of teaching, educating, developing, and spreading the religion of Islam. In relation to the objectives of Islamic boarding schools, it in principle aims to develop Islamic personality, specifically the personality that put more concern on the believing and consciousness of Allah, noble character, piety, usefulness and loyalty to the community, and being a custodian of all humankind (khadim al-ummaħ). The role of Islamic boarding schools in Indonesia was not only as educational institutions but also it took a role as a religious institution operated as a basis against any kind of colonialism, as knowledge institutions, research institutions, training institutions, and community development institutions, and cultural bonds. Keywords: Islamic Boarding Schools, Islamic Educational Institutions, IndonesiaAbstrakTujuan pembahasan ini untuk mengetahui peran pondok pesantren sebagai lembaga pendidikan Islam di Indonesia. Pembahasan ini menggunakan pendekatan kualitatif dan metode studi literatur. Berdasarkan hasil pembahasan, pondok pesantren merupakan lembaga pendidikan Islam yang memberikan pengajaran, pendidikan, pembinaan dan menyebarkan agama Islam. Tujuan pendidikan pesantren adalah dalam rangka membina kepribadian Islami, yaitu kepribadian yang beriman dan bertakwa kepada Allah Subḥānahu Wa Ta’ālâ, berakhlak mulia, bermanfaat dan berkhidmat kepada masyarakat dengan menjadi pelayan umat (khadim al-ummaħ). Peran pondok pesantren di Indonesia bukan hanya sebagai lembaga pendidikan tetapi berperan juga sebagai lembaga keagamaan yang menjadi basis perlawanan terhadap segala bentuk penjajahan, lembaga keilmuan, lembaga penelitian, lembaga pelatihan, dan lembaga pengembangan masyarakat sekaligus menjadi simpul budaya.Kata Kunci: Pondok Pesantren, Lembaga Pendidikan Islam, Indonesia